2021
DOI: 10.2166/bgs.2021.016
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Blue-Green infrastructure as a climate change adaptation strategy: a systematic literature review

Abstract: Blue-Green Infrastructure (BGI) consists of natural and semi-natural systems implemented to mitigate climate change impacts in urban areas, including elevated air temperatures and flooding. This study is a state-of-the-art review that presents recent research on BGI by identifying and critically evaluating published studies that considered urban heat island mitigation and stormwater management as potential benefits. Thirty-two records were included in the review, with the majority of studies published after 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 61 publications
1
24
0
1
Order By: Relevance
“…Additionally, studies (Almaaitah et al, 2021; Voskamp & Van de Ven, 2015; Winker et al, 2019) have also shown that the local use of stormwater (infiltration, retention or irrigation) improves the microclimate within the city. One option is to create retention areas in neighbourhoods, which would work like water squares, providing a public open space throughout the year and becoming large‐volume water collection basins in heavy rainfall events (Voskamp & Van de Ven, 2015; Winker et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies (Almaaitah et al, 2021; Voskamp & Van de Ven, 2015; Winker et al, 2019) have also shown that the local use of stormwater (infiltration, retention or irrigation) improves the microclimate within the city. One option is to create retention areas in neighbourhoods, which would work like water squares, providing a public open space throughout the year and becoming large‐volume water collection basins in heavy rainfall events (Voskamp & Van de Ven, 2015; Winker et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding specific intervention measures, many studies and reviews highlight the social, ecological and economic benefits and downsides of (technical) ecosystem-based adaptations, nature-based solutions, and green infrastructures (roof or facade greening, urban gardens, etc.) [43][44][45][46][47]. Therefore, this section focuses on relevant strategy development and related challenges.…”
Section: State Of the Artmentioning
confidence: 99%
“…Several studies have recommended approaches and considerations for addressing technical challenges. Development of catalogs of different practices and their features, manuals and guidelines, especially for maintenance and monitoring protocols, are among the most frequently proposed solutions (Almaaitah et al, 2021; Geberemariam et al, 2017; C. Li et al, 2019; L. Li et al, 2020; Nickel et al, 2014; Shafique & Kim, 2017). Such solutions become paramount as there is a significant need to inform, educate, and incite the public to maintain these infrastructure practices, especially when upscaling the GSI projects is one of the primary goals.…”
Section: Reviewed Solutionsmentioning
confidence: 99%
“…Several studies have recommended approaches and considerations for addressing technical challenges. Development of catalogs of different practices and their features, manuals and guidelines, especially for maintenance and monitoring protocols, are among the most frequently proposed solutions (Almaaitah et al, 2021;Geberemariam et al, 2017;C. Li et al, 2019;L.…”
Section: Technicalmentioning
confidence: 99%